1998
DOI: 10.1080/00365529850172359
|View full text |Cite
|
Sign up to set email alerts
|

Constipation Assessed on the Basis of Colorectal Physiology

Abstract: About two-thirds of our patients with constipation had objective evidence of delayed transit or pelvic-floor dysfunction. No single test could reliably identify any of the pathophysiologic subgroups of constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Regardless, our study illustrates that some patients can have both dyssynergic defecation and delayed colonic transit. Previous studies have shown that there is an overlap between dyssynergic defecation and slow transit constipation [ 13 , 23 , 24 , 25 ]. Why some patients have both disorders is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, our study illustrates that some patients can have both dyssynergic defecation and delayed colonic transit. Previous studies have shown that there is an overlap between dyssynergic defecation and slow transit constipation [ 13 , 23 , 24 , 25 ]. Why some patients have both disorders is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…As the BET technique was not standardized, the included articles described different methodologies [33, 34, 3943]. Most studies of this meta-analysis described the use of the seated position (12 studies) probably because this method better resembles the act of defecation.…”
Section: Discussionmentioning
confidence: 99%
“…Although probably air simulates inadequately the stool weight and consistency, we did not see any difference in sensitivity and specificity, perhaps because of the low number of patients evaluated (301 out of 1450). Another aspect to take into account is the volume of the balloon—the majority of the studies reported fixed volumes in their series but the volume described varied between 10 mL [45] and 60 mL [43]; in addition, a study described a variable volume (median volume of 250 mL) related to the permanent desire to evacuate [33]. When we use the cut-off of ≥50 mL, the sensitivity and specificity did not change, nor when we exclude only Minguez series (median volume of 250 mL).…”
Section: Discussionmentioning
confidence: 99%
“…FC may result from diverse pathophysiologies, such as delayed colonic transit and/or pelvic floor dysfunction [8]. RH may also be important in the etiology of constipation in some patients, as it is the only demonstrable physiological abnormality in half of such patients [9].…”
Section: Discussionmentioning
confidence: 99%